2009
DOI: 10.1136/bcr.10.2008.1121
|View full text |Cite
|
Sign up to set email alerts
|

Congenital defect of the partial atrioventricular canal with Klinefelter syndrome

Abstract: The case of a 25-year-old man with a partial atrioventricular canal defect (PAVCD) with Klinefelter syndrome is reported here. The patient had Klinefelter syndrome associated with an atrial septal defect and the cleft of the anterior leaflet of the mitral valve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Among 3550 KS subjects, Swerdlow et al (7) reported that CCD was the specific cause of mortality in five patients (Standardized Mortality Ratio = 7.3). To the best of our knowledge, all cases of CCD in KS (68,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94) are fully reported in the Supplemental Data 1, see section on supplementary data given at the end of this article.…”
Section: Structural and Functional Cardiovascular Abnormalities In Klmentioning
confidence: 99%
“…Among 3550 KS subjects, Swerdlow et al (7) reported that CCD was the specific cause of mortality in five patients (Standardized Mortality Ratio = 7.3). To the best of our knowledge, all cases of CCD in KS (68,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94) are fully reported in the Supplemental Data 1, see section on supplementary data given at the end of this article.…”
Section: Structural and Functional Cardiovascular Abnormalities In Klmentioning
confidence: 99%